Program Pembuatan Silase dalam Meningkatkan Ketersediaan Pakan Ternak dan Membangun Kemandirian Peternakan di Desa Keteleng, Batang - Sulastiadi, Abyndra Hinayat; Nugraha, Raikhan Wahid Rif’at Rasendriya; Fauziyah, Deva Aghnia; Zuvian, Nicholas Ilham; Anggerny, Adellia; Ramadhan, Ammar; Setiawan, Alifiannisa Thufailah; Putri, Natasya Permata; Rokhaniah, Siti; Baihaqi, Muhamad (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Silage is a type of animal feed produced through the fermentation of forage materials. This fermentation process is carried out under anaerobic (oxygen-free) conditions, allowing lactic acid bacteria to develop and produce lactic acid while reducing the oxygen content in the forage. The purpose of this program is to produce feed with high moisture content and longer shelf life, making it suitable as a feed reserve during the dry season or when forage resources become scarce. The activities were conducted three times, including presentations on silage, tools and materials, demonstrations, hands-on assistance in silage making, and documentation sessions. Data collection was carried out using participatory observation by directly observing the daily activities of farmers with their livestock. A total of 22 participants took part in this activity. The implementation of the silage-making training had a positive impact on farmers in Keteleng Village. The fermented silage was suitable for livestock consumption. Several challenges were encountered during the program, including limited participation during material presentations and inadequate tools used in the silage-making process. The impact observed was an increase in the farmers' knowledge and understanding of how to make silage as an alternative feed supply through the fermentation process. To ensure the sustainability of this program, active participation of the Keteleng Village farmers was encouraged. The publication of the silage program can further support its continuity. The implementation of this training serves as a concrete step in maintaining feed reserves and improving the welfare of farmers in Keteleng Village, Blado District, Batang Regency, Central Java.